Primary anaplastic extramedullary plasmacytoma in the lacrimal sac - Gupta, Abha; Abhaypal, Khushdeep; Chatterjee , Debajyoti; Kaur, Manpreet; Singh, Manpreet (Digital Journal of Ophthalmology, 2024)
We report the case of a 60-year-old man diagnosed with unilateral, solitary, extramedullary plasmacytoma located in the right lacrimal sac fossa, with no systemic involvement. This rare plasma cell dyscrasia is usually found in the respiratory tract. Clinical and radiological features of the mass and histopathological results are described. The patient was successfully treated with complete surgical excision. There were no clinical or radiological indications of disease recurrence at 10 months’ follow-up.